Cytokinin B-Mo-based Product Influences the Source-to-sink Dynamics and Nonstructural Carbohydrate Contents in Hydroponic Lettuce Plants - Mayra A. Toro-Herrera; Rosa E. Raudales (HortScience)
An understanding of how amendments influence the sink-to-source relationship in leafy crops can be used to optimize plant resource allocation for enhanced growth and quality. Variations in growth rates and carbon pools across individual leaves or groups of leaves at similar developmental stages allow us to comprehend plant strategies of carbon allocation and partitioning. We hypothesized that products enhancing the carbon source-to-sink relationship during leaf development can increase growth and dry matter accumulation. This project aimed to determine whether exogenous applications of a cytokinin-B-Mo-based product during the leaf development of lettuce plants impact the carbon source-to-sink relationship, thus influencing plant growth and quality. The experiment was a complete randomized design with two treatments: a negative control and the application of the product twice during the growing cycle. Each experimental unit consisted of a deep-water culture reservoir with three lettuce plants. Destructive sampling was conducted five times throughout the cycle. At each sampling time (n = 4 per experimental run), the phenological stage was determined, and measurements of root and shoot length, root and shoot dry matter, leaf length, leaf width, leaf area, chlorophyll contents, and nonstructural carbon contents were performed. These data were used to estimate growth indices. The results indicated that the cytokinin-B-Mo-based product increased the number of true unfolded leaves by 1 ± 0.4 and the overall size of the lettuce head by 9%. The treated lettuce reached marketable size 4 days earlier than that of the control treatment. Statistically significant differences were observed in shoot and root dry matter accumulation and foliar length and width at some sampling points. Some growth indices indicate an increase in leaf surface area investment and enhanced conversion efficiency of assimilates into biomass in plants treated with the product. Plants exhibiting these alterations had higher sucrose and total soluble sugar contents. There was a noticeable pattern of higher concentrations of nonstructural carbohydrates, proteins, and amino acids in the leaves compared with those in the roots across all plants and treatments. Overall, the cytokinin-B-Mo-based product appears to strengthen the source-to-sink relationship during lettuce development, resulting in a high-quality plant within a shorter timeframe.